2000
DOI: 10.1080/000368400322453
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between athletic participation and academic performance: evidence from NCAA Division III

Abstract: This paper examines athletes' grades and graduation rates at an NCAA Division III institution. Thirty-seven per cent of all college athletes compete in Division III, yet this group has received little attention in the literature. Nontransfer student-athletes have higher GPAs than nonathletes, while transfer student-athletes have grades similar to nonathletes. Graduation rates are higher for athletes. Thus, athletic participation does not impair students' academic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 12 publications
(13 reference statements)
4
39
1
Order By: Relevance
“…Sports participation also has a significant effect, increasing the likelihood of on-time graduation by around 10%. This result is consistent with a larger literature, which finds high school sports participation raises graduation rate, increases college attendance, and enhances labor market outcomes (Jordan 1999;Robst and Keil 2000;Barron et al 2000). On the other hand, many of the included behavioral factors negatively affect high school graduation, including fighting, smoking, skipping school, having sex and watching television.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…Sports participation also has a significant effect, increasing the likelihood of on-time graduation by around 10%. This result is consistent with a larger literature, which finds high school sports participation raises graduation rate, increases college attendance, and enhances labor market outcomes (Jordan 1999;Robst and Keil 2000;Barron et al 2000). On the other hand, many of the included behavioral factors negatively affect high school graduation, including fighting, smoking, skipping school, having sex and watching television.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…However, students' prior academic achievement has been shown in many empirical studies to be the main influence on how well they perform at university. Studies for the United States that have found a positive relationship between students' university grades and prior academic achievement include Gist et al (1996), Robst and Keil (2000) and Stinebrickner and Stinebrickner (2003). Similar findings have been reported for Australia by Birch and Miller (2005a), Dancer and Fiebig (2004), Dobson and Skuja (2005), Everett and Robins (1991) and Win and Miller (2005), for Canada by Robb and Robb (1999), for the United Kingdom by Johnes (1997), Johnes and McNabb (2004) and Smith and Naylor (2005), and for Singapore by Tay (1994).…”
Section: Introductionsupporting
confidence: 54%
“…The relationship between first‐year academic performance and SES differs from the findings in other studies, which indicate a positive relationship between the two variables (e.g. Gramlich & Greenlee, 1993; Robst & Keil, 2000; Win & Miller, 2005). The finding presented in the present paper may be capturing school‐type effects (which cannot be taken into account).…”
Section: Resultscontrasting
confidence: 99%